PENDUGAAN UMUR SIMPAN FRUIT LEATHER APEL MANALAGI (Malus sylvestris) MENGGUNAKAN METODE ASLT (Accelerated Shelf Life Test) DENGAN MODEL ARRHENIUS - Rizkianiputri, Dini; Atmaka, Windi; Sari, Ardhea Mustika (Universitas Sebelas Maret (UNS), 2016)
Fruit leather is a thin sheet-shaped slurry product with 2-3 mm in thickness, it’s made from dried fruit‘s puree were dried at 50 - 700C. Research on the formulation of fruit leather has been done but the research about the shelf life of fruit leather has not been done. In a previous study, the addition of xanthan gum a binder to improve the quality of manalagi apples fruit leather, where the use of 1,5 gram of xanthan gum provides the best quality, but it is not known the shelf life of the fruit leather. The purpose of this study was to know the shelf life, determine the change in the value of sensory, water content, and total microbial of manalagi apples fruit leather during 25 days of storage and various storage temperature.. The method used was a ASLT method with approach Arrhenius model. Manalagi apples fruit leather stored at 35°C, 45°C, and 55°C were observed on days 0, 5, 10, 15, 20, and 25. The result showed that the quality of each of the tested sensory parameters and moisture contentdecreased from starting day 0 to day 25. The total of microbial are increased from strating day 0 to day 25. Shelf life calculation result of manalagi apples fruit leather based on sensory colour parameter values through the Arrhenius approach on the storage temperature of 30°C is 33.11 days or 1.10 months.